Evaluation of combined use of modified Alvarado score and Ultrasound in predicting acute appendicitis: a prospective study - Kansakar, Nirajan; Agarwal, P. N.; Singh, Rajdeep; Mishra, Anurag; Kumar, Jyoti; Hadke, N. S.; Sheth, Srushti (International Surgery Journal, 2018)
Background: Appendicitis is notorious in its ability to simulate other conditions and accurate diagnosis is imperative for preventing complications of appendicitis on one hand and avoiding negative appendectomy on other. Despite extraordinary advances in modern radiography imaging and diagnostic laboratory investigations, the accurate diagnosis of acute appendicitis remains an enigmatic challenge. Methods: We evaluated 32 patients with features suggestive of acute appendicitis between September 2013 to March 2015. It was a cross-sectional observational study that included modified Alvarado score (MAS) and ultrasound (USG) in predicting appendicitis and correlated both these individually as well as combined, with histopathological findings. Statistical analysis was done by Chi-square test with Yates correction, Fischer’s exact test and unpaired Students’ t test. Results: Ultrasound was found to be more sensitive (74.19%) and accurate (75.0%) as compared to MAS (41.94% and 43.75% respectively). The specificity and positive predictive value (PPV) were similar in both the parameters (100% each). Also, when both the MAS and Ultrasound were combined in predicting acute appendicitis, the sensitivity, negative predictive value and accuracy increased to 80.64%, 14.29% and 81.25% respectively with specificity and PPV being the same as when MAS and USG were considered individually. Conclusions: It is advised that both modified Alvarado score and ultrasound whenever available should be used to predict acute appendicitis to increase the number of positive cases and reduce negative appendectomy and hence reduce the morbidity and mortality.